Prostatic Carcinosarcoma: A Case Report - ÇAM, HAYDAR KAMİL (GALENOS YAYINCILIK, 2017)
Prostatic carcinosarcoma is a rare malignancy composed of sarcomatous and carcinomatous elements. Predominantly, they are very aggressive tumors with a poor prognosis. In this case report, a 78 year-old male patient with prostate adenocarcinoma developing prostatic carcinosarcoma after using androgen blockade for 3 years was presented. We tried to define the clinical and pathological features of this rare malignancy with current information.
Keywords: Prostate; carcinosarcoma; adenocarcinoma; SARCOMATOID CARCINOMA